Application experimental approach to hydration of geosynthetic clay liners by silty sand subsoil under isothermal conditions - Chegenizadeh, Amin; Nikraz, Hamid (2013)
The field performance of Geosynthetic Clay Liners (GCLs) is a topic that is general in scope yet one that deserves discussion, given the scrutiny that these materials have come under during the last decade. In this study, the effect of subsoil moisture on the hydration process of landfill systems was thoroughly investigated. The research focused on the effects of isothermal conditions on the hydration process occurring underneath GCLs. Three GCLs were used in this study. Affecting factors (i.e., subsoil moisture, thermal condition, GCLs types) were examined in this research and the relevant results were presented. The GCLs overlaying 7% soil moisture content only reached a moisture content of 20-30%, providing a very low degree of saturation. In contrast, when the GCLs were overlaying the silty sand at 15% initial moisture content (i.e., close to field capacity) the overall GCL moisture contents reached 90%-160%.